Den nye islandske rettskrivningsordboka - Kristinsson, Ari Páll (Nordiske Studier i Leksikografi, 2007)
Stafsetningarorðabókin (The [Icelandic] Spelling Dictionary), edited by Dóra Hafsteinsdóttir, 2006, can be called the official Icelandic spelling dictionary. It contains ca 65,000 lemmas with ca 73,000 words. In addition, there is a chapter, 61 pp, with com prehensive and detailed rules on Icelandic orthography and punctuation, with various examples. The dictionary shows recommended spelling, and the recommended conjugations and inflections, not only of the traditional vocabulary but of a number of recent loans as well. The present article describes the background to this publication and goes on to discuss the general principles which were followed, as well as some matters of opinion which were dealt with in the editing process, e.g. which inflections were to be recommended, and the amount of loan words adopted in the book.